2021
DOI: 10.1093/infdis/jiab093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonpharmaceutical Interventions for Severe Acute Respiratory Syndrome Coronavirus 2 on Norovirus Outbreaks: An Analysis of Outbreaks Reported By 9 US States

Abstract: In April 2020, the incidence of norovirus outbreaks reported to the National Outbreak Reporting System (NORS) dramatically declined. We used regression models to determine if this decline was best explained by underreporting, seasonal trends, or reduced exposure due to non-pharmaceutical interventions (NPIs) implemented for SARS-CoV-2 using data from 9 states from July 2012–July 2020. The decline in norovirus outbreaks was significant for all 9 states and underreporting or seasonality are unlikely to be the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 13 publications
11
35
0
Order By: Relevance
“…Studies have been recently conducted to show the observed impact of NPIs on a variety of pathogens, including influenza and norovirus, during the COVID-19 pandemic. 5,6 The objective of this study is to identify and synthesize evidence regarding the effectiveness of social distancing NPIs on respiratory infectious viral disease outcomes. This rapid evidence-based review and meta-analysis focuses on studies describing the implementation and assessment of social distancing-related NPIs, including general distancing strategies, quarantine, and/or isolation using single or multiple interventions during respiratory viral epidemics or pandemics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been recently conducted to show the observed impact of NPIs on a variety of pathogens, including influenza and norovirus, during the COVID-19 pandemic. 5,6 The objective of this study is to identify and synthesize evidence regarding the effectiveness of social distancing NPIs on respiratory infectious viral disease outcomes. This rapid evidence-based review and meta-analysis focuses on studies describing the implementation and assessment of social distancing-related NPIs, including general distancing strategies, quarantine, and/or isolation using single or multiple interventions during respiratory viral epidemics or pandemics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been recently conducted to show the observed impact of NPIs on a variety of pathogens, including influenza and norovirus, during the COVID-19 pandemic. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…With the increased public health measures brought on as a result of the recent global coronavirus pandemic, such as school closures, social distancing, and awareness in hygiene practice of frequent handwashing, a number of countries have reported decreases in the number of seasonal viral respiratory infections such as influenza [ 28 , 29 ]. Even a decline in the incidence of norovirus outbreaks in several U.S. states has been associated with the implementation of coronavirus public health measures [ 30 ]. Therefore, modified human behaviors (such as better hygiene awareness, avoidance of crowded conditions, and other disease avoidance lifestyle changes) may potentially delay or reduce the magnitude of the next global pandemic norovirus outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…The unfolding novel coronavirus disease 2019 (COVID-19) pandemic is an unprecedented public health crisis in the modern history of humankind. One collateral consequence of the COVID-19 pandemic is concomitant rapid decline in the incidence of viral gastroenteritis in the rst year of the COVID-19 pandemic, as observed in multiple countries such as China (1), US (2), England (3), Germany (4), Japan (5) and Australia (6). The most likely explanations were sliced testing capacity that led to underreporting and wide implementation of non-speci c non-pharmaceutical interventions for COVID-19 such as frequent handwashing and physical distancing that reduced human-to-human transmission of virus.…”
Section: Introductionmentioning
confidence: 99%